Faktor-faktor yang mempengaruhi profitability pada perusahaan manufaktur di bursa efek indonesia - Edvan Dinardi Wiganda, Sofia Prima Dewi (Jurnal Paradigma Akuntansi, 2019)
The purpose of this research is to obtain empirical evidence about the effect of employee stock ownership program, company efficiency, financial leverage, liquidity, and firm size on the profitability of manufacturing industries listed on the Indonesia Stock Exchange in the period 2015-2017. This study used 64 samples companies that have been selected through a purposive sampling method for three years. The data used were secondary data in the form of financial information from the financial statements and annual reports. The research data was processed using Eviews 10. The results of the research showthat firm size has an effect on profitability, while employee stock ownership programs, company efficiency, financial leverage, and liquidity have no effect on profitability. Suggestions that can be given are for further research to be expected to use other independent variables such as corporate governance, operating cash flow, cash holding, inventory turnover, and net profit margin that may show better results.